Dialectality Measurement: A Research Model for Discussion - Vytautas Kardelis (Lietuvių Kalba)
The aim of this article is to propose a model for studying linguistic behavior and dialectality measurement for scientific discussion. To achieve the goal, the following tasks are set: 1) to briefly review and evaluate the previous studies on linguistic attitudes and linguistic behavior, 2) to systematize the methods of data collection and data analysis, 3) to develop a model for studying linguistic behavior and to present dialectality measurement for discussion.